Analisis faktor risiko bayi Berat Badan Lahir Rendah (BBLR) di Unit Pelayanan Terpadu (UPT) Kesehatan Masyarakat (Kesmas) Gianyar I tahun 2016-2017 - Padma Permana; Gede Bagus Rawida Wijaya (Intisari Sains Medis, 2019)
Background: One of the major causes of newborn mortality is Low Birth Weight (LBW). Each year estimated 15% to 20% of world births or more than 20 million babies are LBW. In UPT Kesmas Gianyar I, there is an increasing trend of LBW incidence from 2014 to June 2017. So, this study aims to determine several risk factors associated with LBW at UPT Kesmas Gianyar I during 2016-2017 period.Methods: A case-control analytic study was conducted among case group of LBW mothers and control group of mothers with normal weight babies in 2017. Selection technique of case group done by total sampling method, while control group by simple random sampling. Data were analysed using SPSS version 21 for Windows and showing in odds ratio, percentage, and p-value.Results: A total of 106 respondens were enrolled in this study whereas each group consists of 53 patients. There was no significant relationship between mother’s age, number of parity, anemia status, nutritional status, and distance of pregnancy with low birth weight incidence (P>0.05). However, multiple pregnancy has shown a significant relationship with LBW (OR: 14.9; 95%CI 3.2-68.5; P=0.0001) as well as gestational age (OR: 3.1; 95% CI 1.02-9.50; P=0.038). Conclusion: Mothers with multiple pregnancies have a 14.9 times risk of having a baby LBW as well as a premature gestational age also have a 3.1 times higher risk of delivering LBW infants.